Effect of Alkaline Surface Modification and Carbonization on Biochemical Properties of Rice and Coffee Husks for Use in Briquettes and Fiber- Reinforced Plastics - Yiga, Vianney Andrew; Lubwama, Michael; Olupot, Peter Wilberforce (Journal of Natural Fibers, 2019)
Effects of alkaline surface modification and carbonization on biochemical properties of selected rice and coffee husk varieties in Uganda were studied. Alkali pre-treatment was done by washing the husks in NaOH at a 15:1 liquor ratio. Pre-treatment is used in biomass conversion to overcome chemical and structural difficulties. Carbonization resulted in production of bio-char. Results showed increased cellulose contents for both the husks and their bio-chars after pre-treatment with NaOH solution. Lignin and hemi-cellulose compositions were reduced after pre-treatment in NaOH solution. Bio-chars for all rice husk varieties showed an increase in lignin content after carbonization. Lignin contents for Robusta coffee husks also increased after carbonization. Cellulose content in bio-chars of both rice and coffee husks reduced drastically after carbonization. A simple regression model relating bulk density and biochemical composition was developed at an accuracy of 70%. Alkaline surface modification and carbonization effects on biochemical properties are due to their impact on the non-cellulosic material and hydrophobicity, respectively, on the fibers.
Keywords: Bio-chemical; Briquettes; Bulk density; Coffee husks; Fiber-reinforced plastics; Hemicellulose